Metazoan parasites of Mexican amphibians and reptiles - Paredes-León, Ricardo; García-Prieto, Luis; Guzmán-Cornejo, Carmen; León-Règagnon, Virginia; Pérez, Tila M. (Zootaxa, 2008)
Based on published records and original data, we present a checklist of metazoan parasites of Mexican amphibians and reptiles. This checklist includes information for 430 nominal taxa of metazoan parasites, 371 helminths (137 trematodes, 10 monogeneans, 29 cestodes, 14 acanthocephalans, 173 nematodes, and 8 hirudineans), 51 acari and 8 crustaceans. We add 184 new locality records to Acari. These data represent the current knowledge on metazoan parasites of 68 amphibians and 219 reptile species of Mexico.